(untitled) (Annals of Medical Research, 2021)
Aim: Enterococci are located in the intestinal flora of animals and humans and have become a major cause of healthcare-associated infections over the years. In this study, related factors were investigated for the isolation of vancomycin-resistant enterococci (VRE) from rectal swab specimens of patients admitted to the internal medicine service.Material and Methods: TRectal swab samples were obtained from 316 patients. VITEK-2 (bioMérieux, Marcy l’Etoile, France) automated system was used for identification of enterococci. Vancomycin susceptibility was studied by Kirby-Bauer disc diffusion method. Resistant strains were confirmed by vancomycin E-test (bioMerieux).Results: VRE was growth in 70 (22.2%) of 316 patients included in the study. According to the univariate analysis results which comparing patients who were colonized with VRE to the control group; These were found, the duration of hospitalization for VRE colonized patients was significantly longer, the usage of glycopeptide and metronidazole increased the VRE colonization and VRE colonized patients were found to have more parenteral feeding. It was determined that hemoglobin, thyroxine and albumin values of patients colonized with VRE were lower. According to the logistic regression analysis, patients with VRE colonization had a higher rate of history in the intensive care unit and higher gamma glutamyl transferase value. Conclusion: It was determined that the hospitalization history in intensive care unit is a risk factor for VRE colonization and especially in patients transported from intensive care unit. Patients colonized with VRE have been found to have higher GGT values and new research on this topic is considered to be needed.